The Simplified Method of Vector Delimitation - Grabiński, Tadeusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The paper presents a graphical procedure for sorting and grouping objects described by a single variable taken in the form of cross-sectional, time series or panel data. This method draws on the classical taxonometric method developed over 100 years ago by Jan Czekanowski. The advantages of simplified vector delimitation are that it is not labour intensive but is intuitive and can be handled with simple spreadsheet functions. The method was used for the taxonomic analysis of a set of 28 EU countries described by three characteristics: the unemployment rate, poverty risk and life expectancy for the two years 2010 and 2015.